E-government Use in Nepal: Issues of Database Management and Data Security - Giri, Shailendra; Shakya, Subarna (Journal of the Institute of Engineering, 2019)
E-government uses information and communication technologies (ICTs) tools and systems to provide better public services. Database Management System (DBMS) is a very significant part in e-governance activities and process in the nation. Security of the data is a main concern of the organizations and private. Proper database management and data security are the major issues in present era. The aim of the paper is to try analyzing necessity of database management and data security. The author used survey methods during research to collect the data and analyze it. This paper concludes that the data backup is key profession while using computer in an institute or people. Hard disk, external hard disk, pen drive, memory card, server and open drive are the major storage Medias. People and employees don’t create backup of data due to lack of knowledge, device and don’t know about importance. The authors conclude that using Antivirus on computer, password on file and computer system, data and information backup, firewall, encryption and decryption technology are the data security tools. Data security protect against the unauthorized use, disclosure, access, destruction, modification and loss of data. Confidential password security and regular monitoring on password are very necessary to secure data. An online security system, as well as manual security systems, should be managed attentively.